Pola Penggunaan Televisi Untuk Pemenuhan Kebutuhan Informasi Dan Peningkatan Keterampilan Bagi Peternak Sapi Potong Di Bojonegoro - Gian Hendra; Amiruddin Saleh; Retno Sri Hartati Mulyandari (Institut Pertanian Bogor, 2016)
Breeding beef cattle is one of the agriculture sector which is very important in Indonesia. In fact the household consumption of beef can’t be fulfilled by the production in the country. The attention to the human resources which arecattle ranchers have a vital role in the form of increasing knowledges and skills to advance the production of beef cattle. Television is one of a mass media that has potential to increase farmers’ knowledges like cultivation knowledgeand marketing knowledge in Ngantru Village, Bojonegoro District, East Java Province. The purpose of this research are 1) to analyze the characteristics, motives and patterns of breeder cattle in watching television, 2) to analyze therelation between the motifs and patterns of breeder cattle watching television with the information needs of breeding beef cattle, 3) to analyze the relation between farmers beef cattle in watching the television with the fulfillment ofinformation needs of beef cattle breeding, and 4) to analyze the relation between the information needs of farmers skills in beef breeding. This study was designed as a survey research, with a quantitative approach supported by qualitative data with the number of respondents which are 50 people selected randomly. Analyzed using descriptive statistics and inferential statistical with Chi-Square analysis test and Spearman Rank test. The results of this research is there is a real connection between the level’s of ownership of livestock with a duration of watching television. The entertainment motif has related with beef cattle farmers’ pattern in watching television, like the frequency and duration. The frequency of beef cattle farmers in watching television also related with entertainment needs.Keywords: cattle breeding, information needs, motif, scheme, television